PERANCANGAN FOOD COURT DI KOTA PONTIANAK - Jacksons Jacksons; Lestari Lestari; Valentinus Pebriano (JMARS: Jurnal Mosaik Arsitektur, 2022)
Pontianak is one of the developing cities. Various culinary businesses are developing in Pontianak, such as catering businesses, restaurants, food courts, street stalls / street stalls. Culinary needs are not only as a fulfillment of basic needs but have also developed into a lifestyle. This is inseparable from the daily life of urban people who have a high level of mobility. People prefer to eat outside the home because it is more practical and also the need for entertainment after a day of activities. Food Court is an alternative that can accommodate and introduce various types of local and non-local foods and can meet the lifestyle of urban people and entertainment. In addition, the phenomenon of the Covid-19 pandemic emerged which became the basis for people's concerns. Covid-19 greatly affects people's mind preferences for the ease of being infected and tend to choose open spaces. Therefore, it is necessary to design a food court in Pontianak that emphasizes open space. This design is carried out through data collection, followed by the analysis stage to obtain spatial layout and design concepts with the final result in the form of visualization and design work drawings. The design location is on Jalan Abdulrahman Saleh, Bangka Belitung Laut District, Southeast Pontianak District, Pontianak City, West Kalimantan. The shape of the building is adapted to modern architecture containing food and beverage outlets, as well as facilities for visitors.